2010
DOI: 10.1007/s00125-010-1970-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two sulfonylureas with high and low myocardial KATP channel affinity on myocardial infarct size and metabolism in a rat model of type 2 diabetes

Abstract: Aims/hypothesis Sulfonylureas (SUs) may impair outcome in patients with acute coronary syndrome. Most experimental studies of the myocardial effects of SU treatment are performed in non-diabetic models. We compared the effect of two widely used SUs, glibenclamide (gb) and gliclazide (gc), with high and low myocardial K ATP channel affinity, respectively, at therapeutic concentrations on infarct size, left ventricular (LV) function and myocardial glycogen, lactate and alanine content before and after ischaemia/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…[153]  GK rat: Refs. [153, 154] No change in infarct size  STZ (±alloxan)-induced DM (dog, rabbit, rat, mouse): Refs. [147, 149, 150, 155165]  GK rat: Refs.…”
Section: Myocardial Tolerance Against Ischemia/reperfusion-induced Nementioning
confidence: 99%
“…[153]  GK rat: Refs. [153, 154] No change in infarct size  STZ (±alloxan)-induced DM (dog, rabbit, rat, mouse): Refs. [147, 149, 150, 155165]  GK rat: Refs.…”
Section: Myocardial Tolerance Against Ischemia/reperfusion-induced Nementioning
confidence: 99%
“…With a few exceptions [30,31], DM models with obesity and hyperinsulinemia showed increased myocardial susceptibility to ischemia/reperfusion-induced necrosis [32-41]. In contrast, high glucose level induced simply by glucose or dextrose infusion did not affect infarct size in the majority of studies, including two recent studies [42,43] (Table 2).…”
Section: Changes In Myocardial Susceptibility To Infarction By Dmmentioning
confidence: 99%
“…However, since they used a PC protocol with multiple cycles of ischemia/reperfusion only, the change in the threshold for inducing PC protection might have been missed in their study. In fact, impairment of PC by DM has been observed in multiple species (rats, rabbits and dogs) and different models of DM (STZ-induced type 1 DM and genetic models of type 2 DM) [30,37,50-54]. Mimetics of ischemic PC and PostC (diazoxide, erythropoietin, [D-Ala 2 , D-Leu 5 -enkephalin acetate [DADLE] and isoflurane) were also ineffective for limitation of infarct size in DM hearts [33,34,37,55-59], confirming that DM impairs intracellular signaling mechanisms relevant to myocardial protection.…”
Section: Defects In Intracellular Protective Signaling In Dm Heartsmentioning
confidence: 99%
“…The extra-pancreatic cardiovascular effects of glyburide and repaglinide may potentially increase the risk of adverse cardiovascular events. In contrast, gliclazide appears to be more selective for SUR1, which may confer a better cardiovascular prognosis during acute ischemic events (Abdelmoneim et al, 2012;Kristiansen et al, 2011). Indeed, we have shown previously that gliclazide use is associated with a lower risk of acute coronary syndrome-related morbidity and mortality compared to glyburide use (Abdelmoneim et al, 2014).…”
Section: Introductionmentioning
confidence: 86%
“…Some IS, like glyburide and the non-sulfonylurea IS repaglinide, will bind to both SUR1 and SUR2 isoforms when given at usual therapeutic doses and therefore also inhibit K ATP channels located in the myocardium and vascular smooth muscle cells (Abdelmoneim et al, 2012). Animal models have shown that cardiac K ATP channel opening is protective during ischemia-reperfusion injury and that K ATP channel activity is essential for ischemic conditioning, an endogenous protective mechanism that promotes salvage of myocardial tissue during ischemia-reperfusion injury (Kristiansen et al, 2011;Tang et al, 2006). The extra-pancreatic cardiovascular effects of glyburide and repaglinide may potentially increase the risk of adverse cardiovascular events.…”
Section: Introductionmentioning
confidence: 98%